Poverty and Landownership - Moene, Karl Ove (American Economic Review, 1992)
I study how landownership affects labor allocation, income distribution, and poverty in less developed countries. I focus on three prototypes of ownership classes: landlords, smallholders, and landless people. Agents are identical except for their ownership of assets. On the basis of optimizing behavior, they divide into urban workers in the modern sector, urban workers in the informal sector, agricultural laborers, subsistence farmers, and landlords. The impact of land reform on production and poverty depends on the amount of fertile land per capita. A more egalitarian distribution of landownership reduces poverty where land is scarce but not where land is abundant.